Groupoid C*-Algebras - Madalina Roxana Buneci (Surveys in Mathematics and its Applications, 2006)
The purpose of this paper is to recall the main ingredients of the construction of the C*-algebra of a groupoid (introduced by Renault in [A groupoid approach to C*-algebras, Lecture Notes in Math., Springer-Verlag, 793, 1980]) and to collect some results on the independence of the C*-algebra on the choice of Haar system.